(3LGeY GdCMcGe aj eYQaI GdMdGd hGdMQGes - (3YHO Gddg Hf eMeO QVG THQ GdMSjfj GdcGXej,J (B1242 (3g` s
(3ChdgG (B:s
(3CeG HYO gPG gh GdeLdO GdKGfi ef cJGH LGeY GdeYGQa hGdCMcGe s
(3BNQgG (B:s
(3cGfJ HdbjS edcI SHC s
(3HgG fXGe GdJYbjHIs
(3cJHJ gPg GdfSNI HCcKQ ef NWs
(3fSNI KGfjI ef Qbe (B75 (3abg ePGgH CNQis
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3abg GdePGgH GdCNQis